THE SUSTAINABILITY REPORTS ISSUED – AN INFLUENTIAL FACTOR FOR THE STOCKS QUOTATIONS? - MOROȘAN Adrian (Management of Sustainable Development)
The integration of sustainability in economics is essential for achieving long-term economic stability and environmental preservation. As climate change, resource depletion, and social inequities intensify, adopting sustainable practices within economic frameworks is crucial. This article delves into the relationship between sustainability and economics, highlighting the impact of non-financial factors, such as sustainability reports, on financial outcomes like stock prices. By analysing the Romanian BET index, we examine the correlation between sustainability practices and market value. Our findings indicate that the visibility of sustainability reports on company websites does not significantly affect stock prices. However, the general upward trend in stock quotations suggests that other factors might play a more substantial role. This study underscores the importance of regulatory frameworks in promoting transparent sustainability practices. Future research will expand this analysis to global markets, aiming to develop a comprehensive company score that incorporates various financial and non-financial factors.